THE EFFECT OF EXTRA FOODING ON THE FATIGUE OF FIELD WORKERS (TECHNICAL SERVICES) AT PT PLN (PERSERO) ULP MEDAN SELATAN - Halijah, Siti; Salianto, Salianto; Suherry, Kadillah; Khairunnisa, Rizki; Aprilia, Putri Dwita; Wirdayani, Annisa; Batubara, Layla Hanum; Aritonang, Alifia Octaviani; Adisti, Putri; Wulandari, Dea Ayu Tri (HEARTY, 2024)
This research aims to investigate the effect of extra fooding on the fatigue of field workers at PT PLN (Persero) ULP Medan Selatan. This study considered the impact of additional food intake on fatigue levels, taking into account factors such as physical activity, rest time, working environment conditions, and the type of additional food consumed. The quantitative research method involved 20 engineering service workers who were given additional food in cucumber juice and coconut water. Data was collected before and after consuming extra food, with fatigue levels measured using a psychometrically tested rating scale. Descriptive statistical and regression analyses were performed to establish the relationship between extra food consumption and changes in fatigue levels. The results show that extra fooding has the potential to reduce fatigue in field workers, but the impact may vary depending on contextual factors. In conclusion, a holistic and integrated approach is needed in managing worker fatigue in the field, considering nutritional aspects and other factors that influence their working conditions.